GBSS:researches on group-based semantic search - CHEN Hai-tao; GONG Zheng-hu; HUANG Zun-guo (Tongxin xuebao)
A group-based semantic search method-GBSS was presented.With regard to architecture,GBSS introduced a hybrid architecture in which the storage and search of raw data was based on DHT network,but the storage and search of meta-data was based on unstructured P2P network.With regard to search algorithm,GBSS presented a file grouping method without users’ description and constructs friend relations between nodes based on search interests and sharing files.The design idea came from some conclusions of P2P researches and complex network researches.The forwarding of user requests came use of friend relations in search process,which integrated effective caching strategy.The simulation tests prove that the GBSS algorithm is efficient,stable,and the performance improved times compared with traditional algorithms.